Vitamin D/vitamin D receptor protects intestinal barrier against colitis by positively regulating Notch pathway - Li, Yanni; Guo, Yaoyu; Geng, Chong; Song, Shuailing; Yang, Wenjuan; Li, Xiao; Wang, Chunhui (Frontiers in Pharmacology, 2024)
Objective: Vitamin D/Vitamin D receptor (VD/VDR) signaling and the Notch pathway are involved in intestinal barrier restoration in colitis; however, their relationship and underlying mechanism are largely unknown. Therefore, this study aimed to investigate the role and mechanism of VD/VDR and the Notch pathways in intestinal barrier protection. Methods: Genetic Vdr knockout (VDR KO) and VD deficient (VDd) mice were established, and colitis was induced by feeding 2.5% dextran sodium sulfate (DSS) water. Mechanistic studies, including real-time PCR, immunofluorescence, western blotting and dual-luciferase reporter assays, were performed on cultured Caco-2 cells and intestinal organoids. Results: VD deficiency and VDR genetical KO increased the severity of DSS-induced colitis in mice, which presented a higher disease activity index score, increased intestinal permeability, and more severe intestinal histological damage than controls, accompanied by decreased and disrupted claudin-1 and claudin-3. Moreover, inhibition of Notch pathway by LY411,575 aggravated the severity of DSS-induced colitis and intestinal injury. In Caco-2 cells and intestinal organoids, the expression of Notch-1, N1ICD and Hes1 decreased upon downregulation or KO of VDR but increased upon paricalcitol (PAR, a VDR agonist) treatment. Meanwhile, PAR rescued claudin-1 and claudin-3 impairments that resulted from TNF-α exposure but failed to restore claudin-3 upon Notch inhibition. The dual-luciferase reporter assay further suggested that VD/VDR positively regulated the Notch signaling pathway by modulating Notch-1 transcription. Conclusions: VD/VDR positively modulates Notch activation by promoting Notch-1 transcription to maintain intestinal tight junction integrity and barrier function. This highlights the VD/VDR-Notch pathway as a potential new therapeutic target for protecting the intestinal barrier against ulcerative colitis.